2022
DOI: 10.1007/s10055-022-00685-9
|View full text |Cite
|
Sign up to set email alerts
|

The sentiment of a virtual rock concert

Abstract: We created a virtual reality version of a 1983 performance by Dire Straits, this being a highly complex scenario consisting of both the virtual band performance and the appearance and behaviour of the virtual audience surrounding the participants. Our goal was to understand the responses of participants, and to learn how this type of scenario might be improved for later reconstructions of other concerts. To understand the responses of participants we carried out two studies which used sentiment analysis of tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…We did not implement the whole questionnaire since we only used it as a control question which was not a part of our statistical analysis. We anticipated that the behavioral response itself will be a strong predictor of presence, or rather place and plausibility illusions as discussed in Slater et al [45]. Similarly, we selected only the relevant questions of agency and body ownership from the Embodiment Questionnaire [46] as embodiment was not the focus of our study.…”
Section: Methodsmentioning
confidence: 99%
“…We did not implement the whole questionnaire since we only used it as a control question which was not a part of our statistical analysis. We anticipated that the behavioral response itself will be a strong predictor of presence, or rather place and plausibility illusions as discussed in Slater et al [45]. Similarly, we selected only the relevant questions of agency and body ownership from the Embodiment Questionnaire [46] as embodiment was not the focus of our study.…”
Section: Methodsmentioning
confidence: 99%
“…The current study has its limitations. Firstly, as research focusing on immersive virtual concert experiences is still in its infancy (Onderdijk et al 2021;Slater et al 2022), rather than using more in-depth qualitative and/or quantitative methods, we opted to take a broad, exploratory view using a mixed-method approach. Our methods provided a variety of novel findings on such experiences, which can be further elaborated on in more in-depth future work.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Virtual reality (VR) has been an invaluable tool in the study of human behavior and emotional arousal in crowds (Somarathna et al, 2022), offering precise control and the replication of parameters of the virtual crowds across multiple participants with a detailed assessment of individual data. For example, a study exploring people's responses to being part of a virtual rock concert audience found that negative sentiments sometimes resulted from interactions with the virtual audience and that the illusion of being at the concert was associated with positive sentiment for men but negative sentiments for women (Beacco et al, 2021;Slater et al, 2022). Dickinson et al (2019) found a significant increase in negative effects as the density of a virtual crowd increased.…”
Section: Introductionmentioning
confidence: 99%